Audio Test for Musicality: Designing A Technology-Based Instrument for Measuring Music Learning Outcomes - Salafiyah, Nafik; Wadiyo, Wadiyo; Aesijah, Siti; Nuswantara, Deu Aditama (Jurnal Seni Musik, 2023)
The Musicality Assessment Test is a notation-based examination covering three concepts: ear training, listening, and reading. Due to the incorporation of these three conceptual domains, the musicality test can only be effectively conducted when the test questions are presented in audio format. The aim of this study was to innovate the testing process as a means of assessing music learning outcomes through an audio-based format. This study employed qualitative descriptive method, and utilized Sibelius and Cubase software as technological tools. The design phase began with the preparation of the structured test instrument, followed by the recording process using Sibelius software. This involved recording questions related to rhythmic, pitch, interval, melodic, scale, and harmonic notation, which were then transformed into MIDI format. Cubase software was employed for combining human voice with MIDI in the recording process. The testing instrument was meticulously crafted as an innovative product, ready for trial to measure the musicality abilities of test takers. The test tool was designed as an innovative product, poised for use in assessing the musicality skills of test takers.